Altered Physical Performance Following Advanced Special Operations Tactical Training. Issue 7 (July 2021) - Winters, Joshua D.; Heebner, Nicholas R.; Johnson, Alexa K.; Poploski, Kathleen M.; Royer, Scott D.; Nagai, Takashi; Randall, Carson A.; Abt, John P.; Lephart, Scott M.
Abstract : Abstract: Winters, JD, Heebner, NR, Johnson, AK, Poploski, KM, Royer, SD, Nagai, T, Randall, CA, Abt, JP, and Lephart, SM. Altered physical performance following advanced special operations tactical training. J Strength Cond Res 35(7): 1809–1816, 2021—The purpose of this study was to determine how the unique challenges of specific military tactical training phases influence overall physical performance characteristics. Broad jump, 5-10-5, 300-yd shuttle, percent body fat (%BF), anaerobic power (AP) and anaerobic capacity (AC), maximal oxygen uptake (V[Combining Dot Above]O2 max), isokinetic knee extension/flexion strength, shoulder internal/external rotation strength, and trunk extension/flexion strength were collected on 73 United States Marine Corps Forces Special Operations Command (MARSOC) students (age: 27.4 ± 3.8 years, height: 178.7 ± 6.6 cm, and body mass: 85.8 ± 9.4 kg) at the beginning of (P1), in between (P2), and at the completion of 2 distinct tactical training phases (P3). Linear mixed models were used to analyze within-subject performance changes over the 3 time points, and post hoc Bonferroni pairwise comparisons analyzed performance changes between each testing time point. There were significant changes in broad jump ( p < 0.0001), 5-10-5 agility time ( p < 0.001), %BF ( p = 0.011), AP ( p < 0.0001), V[Combining Dot Above]O2 max ( p = 0.001), and both right and left shoulder internal rotation strength ( p = 0.004 and p = 0.015, respectively) between P1 and P2. There were also significant changes in 300-yd shuttle run time ( p = 0.001), AP ( p < 0.0001), AC ( p < 0.0001), left knee extension strength ( p = 0.006), trunk flexion strength ( p < 0.0001), and left shoulder external rotation strength (0.027) between P2 and P3. Identifying the effect that specific tactical training phases may have on physical performance will allow for the development of effective phase-specific evidence-based human performance programs, reducing performance deficits and thereby reducing the risk of injury.